Management of Machining Practice Learning Industrial Product Based - Yudiono, Heri (Journal of Vocational and Career Education, 2020)
The development of vocational practice learning must adapt to the needs of contemporary industry competencies. Vocational practice learning innovations must be carried out appropriately, systematically by taking into account the needs of the environment. The selection of the right learning model affects the process, learning outcomes, and student learning experience. This study aims to analyze the process of learning industrial product-based machining practices. The research approach used an experiment with a static group comparison design. The design of this study used two groups consisting of an experimental group and a control group. The experimental group is the group that gets treatment using industrial product-based practical learning, while the control group uses practical learning based on assignment job sheets. The choice of the two groups was done randomly. Each group consists of 20 respondents. The research respondents were students of the Department of Mechanical Engineering UniversitasÃ‚Â  Negeri Semarang who met the requirements and had passed the Machining Process 1 course. The results revealed that there were differences in the process of implementing the learning practice of industrial product-based machining and learning the practice of machining based on job sheet assignments. The difference in the learning process between the two groups is about the process of giving apperception and motivation, mastery of learning materials, implementing learning strategies, choosing the application of learning resources or learning media, involving students in learning, and closing learning activities.